Ivorian Towns of the Inland, Put to the Test of Their Environmental Degradation: the Case of Daloa (West Center of Côte d'Ivoire) - Abel, Bolou Gbitry; Didier-Charles, Gouaméné; Xavier, Bleu Dion (Environmental Management and Sustainable Development, 2021)
With its 258,509 inhabitants (INS, 2014. 27), Daloa, the third largest city in Côte d'Ivoire, has experienced an urban growth rate of 2.73% (op cites). But over the years, the locality has been confronted with an uncontrolled urban dynamic which has environmental repercussions on its landscape. Measures and actions are daily announced by the public authorities to eradicate this phenomenon, but the change is still virtual. This study aims to identify the persistence of environmental degradation in the city of Daloa. The methodology for conducting this study was based on a set of technical approaches. This is documentary research focusing mainly on scientific work and study reports addressing the issue of uncontrolled urbanization and its environmental effects. In addition to this approach, direct observation and interviews with local resource people were used. A questionnaire survey was also conducted with 373 heads of household using the probabilistic formula without replacement in 1/3 of the enumeration areas totaling 13 neighborhoods. The results show that the deterioration of the urban environment in Daloa is experienced by households in the form of pollution caused by rainwater, wastewater and sluices (47%.), Pollution due to household waste (24% ), air (15%) and noise (14%) pollution. The factors are plural and reveal that 58% of the households surveyed dispose of their used water (detergents, dishes) on the street and 48% dump household waste on the streets. The impact on the urban landscape is just as diverse and unpleasant. Rainwater on unpaved roads accelerates erosion. The flow of open sewage and piles of rubbish, undermine the aesthetics of the urban landscape of Daloa.